Long‐term safety and efficacy of the sodium–glucose cotransporter 2 inhibitor, tofogliflozin, added on glucagon‐like peptide‐1 receptor agonist in Japanese patients with type 2 diabetes mellitus: A 52‐week open‐label, multicenter, post‐marketing clinical study. Issue 6 (28th May 2019) - Terauchi, Yasuo; Fujiwara, Hisataka; Kurihara, Yuji; Suganami, Hideki; Tamura, Masahiro; Senda, Masayuki; Gunji, Ryoji; Kaku, Kohei
Abstract: Aims/Introduction: Tofogliflozin is a potent and highly selective sodium–glucose cotransporter 2 inhibitor that is currently used to treat patients with type 2 diabetes mellitus. The aim of the present study was to evaluate the safety and efficacy of tofogliflozin add‐on to glucagon‐like peptide‐1 (GLP‐1) receptor agonist monotherapy. Materials and Methods: In this 52‐week, prospective, multicenter, single arm, post‐marketing clinical study, Japanese patients who had already been receiving GLP‐1 receptor agonist monotherapy for ≥8 weeks, glycated hemoglobin ≥7.0 and <10.5%, and body mass index ≥18.5 and <35.0 kg/m 2 were enrolled. Tofogliflozin 20 mg was orally administered once daily for 52 weeks with GLP‐1 receptor agonist. Primary end‐points were safety and change in glycated hemoglobin from baseline to week 52. Safety was assessed on the basis of the adverse events. Changes from baseline in fasting plasma glucose, bodyweight, blood pressure, uric acid and lipid parameters were assessed as secondary efficacy end‐points. Results: Of the 67 patients enrolled, 63 patients completed the study. Overall, 26 adverse drug reactions occurred in 17 patients (25.4%). Adverse drug reactions with a frequency of two or more patients (3.0%) were constipation, thirst, dehydration and pollakiuria. Hypoglycemia ( n  = 1) was limited. With the addition of tofogliflozin to GLP‐1 receptor agonist, the subsequent mean (standard deviation) reduction in glycated hemoglobin was −0.6% (1.0%; P  <   0.0001). Fasting plasma glucose, bodyweight and blood pressure were significantly improved. Conclusions: Tofogliflozin add‐on to GLP‐1 receptor agonist monotherapy is an effective treatment option with an acceptable safety profile. Abstract : We carried out a 52‐week, multicenter, single‐arm, clinical trial in Japanese patients with type 2 diabetes mellitus, and here reported the results of a 52‐week analysis. No new safety concerns were identified. Glycated hemoglobin, fasting plasma glucose, bodyweight and blood pressure were significantly improved.